2010
DOI: 10.1093/rheumatology/keq324
|View full text |Cite
|
Sign up to set email alerts
|

Registries in rheumatological and musculoskeletal conditions. Paediatric Behcet's disease: an international cohort study of 110 patients. One-year follow-up data

Abstract: The expert committee has classified the majority of patients in the BD group although they presented with few symptoms independently of BD classification criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 17 publications
4
42
2
Order By: Relevance
“…Behçet's syndrome (BS) is a systemic, chronic relapsing vasculitis, typically characterized by recurrent oro-genital ulcers, ocular inflammation and skin manifestations; articular, vascular, gastro-enteric and neurological involvement may also occur [1][2][3]. Even though the aetiology of BS is still unknown [4][5][6], recently, the combination of clinical features, lack of autoantibodies and beneficial effects derived from IL-1 inhibition has reinvigorated the concept of BS as an autoinflammatory disease [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Behçet's syndrome (BS) is a systemic, chronic relapsing vasculitis, typically characterized by recurrent oro-genital ulcers, ocular inflammation and skin manifestations; articular, vascular, gastro-enteric and neurological involvement may also occur [1][2][3]. Even though the aetiology of BS is still unknown [4][5][6], recently, the combination of clinical features, lack of autoantibodies and beneficial effects derived from IL-1 inhibition has reinvigorated the concept of BS as an autoinflammatory disease [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Our study results suggest that more than one clinical phenotype is present in patients with MWS, complicating the effort of developing diagnostic criteria. Koné-Paut et al recently suggested more than one set of criteria is required for Behçet's disease, a polygenetic autoinflammatory disease (36), since adult criteria perform poorly in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of disease occurs before 16 years in 4-26% of the patients with Behçet's disease. Although it is observed with a two-fold higher frequency in male patients in adults, gender difference is not observed in children (53,54). However, neurological involvement in Behçet's disease is observed with a 5.5-fold higher frequency in male patients (53).…”
Section: Behçet's Diseasementioning
confidence: 92%
“…Uveitis is mostly in the form of panuveitis and is observed more frequently and has a more severe prognosis in male patients. In addition, it has been reported that genital ulcers are observed more frequently in girls (54).…”
Section: Behçet's Diseasementioning
confidence: 99%